2007
DOI: 10.1557/proc-0994-f04-02
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Irradiation Damage in Single-Walled Carbon Nanotubes

Abstract: We show that low-energy (20 eV–20 keV) electron or photon irradiation extinguishes the characteristic physical and chemical properties of single-walled carbon nanotubes, indicating that the irradiation damages the nanotubes. The irradiation-induced defects convert the electric properties of metallic SWNTs to semiconducting, and the nominal bandgap can be tuned simply by the irradiation dose. The defects also have the following interesting properties. The damage and recovery are reversible, indicating that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…2 and 3 are consistent with each other. They are also consistent with previous studies using on-substrate SWNT devices [5][6][7][8]. Theoretical calculations have shown that a high electric field of ∼1 V·nm −1 barely opens a band gap of several ten millielectron volts.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…2 and 3 are consistent with each other. They are also consistent with previous studies using on-substrate SWNT devices [5][6][7][8]. Theoretical calculations have shown that a high electric field of ∼1 V·nm −1 barely opens a band gap of several ten millielectron volts.…”
Section: Resultssupporting
confidence: 92%
“…A moderate irradiation can convert the room temperature electric properties of a metallic SWNT to semiconducting [4]. An intensive irradiation finally makes a SWNT almost insulating [5][6][7][8]. The decreased conductivity with the irradiation, as well as the degraded Raman and PL spectra, can recover reversibly by annealing [1,3,6] or applying a high bias to the SWNTs [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations